Bowling Challenge - Anon (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Occupational Safety and Health Department, Universiti Malaysia Perlis (UniMAP), 3rd April 2011 at Perlis Bowl, Kangar, Perlis, Malaysia.